BMI may underestimate the socioeconomic gradient in true obesity. Issue 3 (3rd January 2013) - van den, G.; van, M.; Vrijkotte, T. G. M.; Gemke, R. J. B. J.
Summary Background Body mass index (BMI) does not make a distinction between fat mass and lean mass. In children, high fat mass appears to be associated with low maternal education, as well as low lean mass because maternal education is associated with physical activity. Therefore, BMI might underestimate true obesity in children of low‐educated mothers. Objective To investigate the associations of maternal education with fat mass index (FMI), lean mass index (LMI) and BMI. Methods In total, 1965 Dutch children from a prospective cohort, aged 5.7 years (standard deviation 0.5), had available data on body composition based on bioelectrical impedance analysis. Results Maternal education was not associated with BMI after adjustment for confounders. In contrast, children of low‐educated mothers had a higher FMI (β 0.28 95% confidence interval [CI] 0.07; 0.49) and a lower LMI (β −0.18 95% CI −0.33; −0.03) compared with children of high‐educated mothers. Conclusions This suggests that BMI underestimates the educational gradient of childhood obesity.